Preparation of Fe2O3/WS2 heterostructures with enhanced photocatalytic performances for dye degradation and Cr (Ⅵ) reduction. Issue 1 (12th August 2022) - Jia-nan, Yin; Shu, Wang; Yong-xin, Jiao
Abstract: In the present study, a two-step hydrothermal method was employed to synthesize Fe2 O3 /WS2 composites with flower-like structure, which performed significant photocatalytic activities compared with the bare components. The morphologies and structures of the as-prepared photocatalysts were characterized, as well as the surface chemical components and the optical properties. Afterwards, the photocatalytic properties of the catalysts were evaluated through degrading MB dye and reducing Cr (VI) under the simulated solar-driven irradiation. Among these photocatalysts, 2WF behaved an efficiently oxidation degradation of 20 mg/L MB solution within 20 min, more than 5 times of bare Fe2 O3 nanoparticles and nearly 3 times of bare WS2 nanosheets. Besides that, it exhibited an excellent photocatalytic reduction activity on reducing 40 mg/L Cr (VI) solution within 80 min, which was far superior to bare Fe2 O3 and WS2 . The excellent photocatalytic oxidation and reduction abilities enabled Fe2 O3 /WS2 heterostructures to be applied in the field of organic and inorganic pollutant decontaminations.